Time to Development of Anemia and Predictors among HIV-Infected Patients Initiating ART at Felege Hiwot Referral Hospital, Northwest Ethiopia: A Retrospective Follow-Up Study - Manaye, Yibekal (Biomed Res Int, 2020)
METHODS: A retrospective follow-up study was conducted among clients on ART from 2012 to 2017. Data were collected using checklists. The Kaplan-Meier curve was employed to compare survival rates. The Cox proportional hazard model was applied to identify predictors of time to development of anemia. RESULTS: A total of 490 ART patients were followed. The overall incidence of anemia was 27/100 person-years. The incidence was highest in the second year (18.7/100 PY) of starting ART when compared with the first year (13.8/100 PY) and third year (18.1/100 PY) of ART initiation. The independent predictors show an association for time to development of anemia and were as follows: being female (AHR = 2.94, 95%CI = 2.15–4.0), pulmonary tuberculosis positive (AHR = 2.98, 95%CI = 1.62–5.51), baseline weight < 60 kg (AHR = 1.51, 95%CI = 1.19-1.92), and severe acute malnutrition (AHR = 2.0, 95%CI = 1.39-2.89). CONCLUSION: Most of the anemia cases occurred after the first year of ART initiation. Pulmonary tuberculosis, baseline weight, nutritional status, and sex were predictors for anemia. Clients with low baseline weight and abnormal nutritional status need to get close follow-up to prevent the risk of early development of anemia.